Lourdes Arizpe A Mexican Pioneer in Anthropology - Arizpe, Lourdes (SpringerBriefs on Pioneers in Science and Practice, 2014)
This book presents major texts by Prof. Dr. Lourdes Arizpe Schlosser, a pioneering Mexican anthropologist, on the occasion of her 70th birthday. She is a leading researcher into indigenous peoples, an innovator in women's studies and a global scientific leader who has inspired the international research and policy communities. Throughout her distinguished career she has analysed ethnicism and indigenous peoples, women in migratory flows, cultural and social sustainability and intangible cultural heritage as social capital, placing these issues on the world agenda for research and policy. Several of the 12 major texts in this volume have been published since 1972 in the US, Europe, Latin America and India; some were first published in Spanish and are available in English for the first time. This anthology also includes recent unpublished texts on culture, development and international cultural policy delivered at high-level international meetings.